Polyisoprenylated Acylphloroglucinols from Garcinia nervosa - Nugroho, Alfarius Eko; Nakamura, Hitomi; Inoue, Daisuke; Hirasawa, Yusuke; Wong, Chin Piow; Kaneda, Toshio; A. Hadi, A. Hamid; Morita, Hiroshi (SAGE Publications, 2018)
Two new polyisoprenylated acylphloroglucinols, 7-epi-isoxanthochymol and 7-epi-cycloxanthochymol (1 – 2), were isolated from the barks of Garcinia nervosa together with their 7-epimers isoxanthochymol (3) and cycloxanthochymol (4). Their structures were determined on the basis of NMR spectroscopic data. The cytotoxic activity of the isolated compounds against HL-60, MCF-7 (human breast adenocarcinoma), A549 (human lung adenocarcinoma) and HepG2 (human hepatocellular carcinoma) cells were evaluated, and all compounds showed cytotoxic activity against all cell lines.